Cervical fluid calreticulin and cathepsin-G in pregnancies complicated by preterm prelabor rupture of membranes - Andrys, Ctirad; Kacerovská Musilová, Ivana; Drahosova, Marcela; Soucek, Ondrej; Pliskova, Lenka; Jacobsson, Bo; Zhong, Nanbert; Kacerovsky, Marian (Journal of maternal-fetal & neonatal medicine, 2018)
OBJECTIVE: The study aimed to determine the cervical calreticulin and cathepsin-G concentrations in pregnancies complicated by preterm prelabor rupture of membranes (PPROM) with respect to the presence of microbial invasion of the amniotic cavity (MIAC) and intra-amniotic inflammation (IAI). METHODS: Eighty women with singleton pregnancies complicated by PPROM were included in this study. Cervical and amniotic fluids were obtained at the time of admission, and concentrations of calreticulin and cathepsin-G in cervical fluid were determined using ELISA. The MIAC was defined as a positive PCR analysis for Ureaplasma species, Mycoplasma hominis, and/or Chlamydia trachomatis and/or by positivity for the 16S rRNA gene. IAI was defined as amniotic fluid bedside IL-6 concentrations ≥745 pg/mL Result: Neither women with MIAC nor with IAI had different cervical fluid concentrations of calreticulin (with MIAC: median 18.9 pg/mL vs. without MIAC: median 14.7 pg/mL, p = 0.28; with IAI: median 14.3 pg/mL vs. without IAI: median 15.6 pg/mL, p = 0.57;) or of cathepsin-G (with MIAC: median 30.7 pg/mL vs. without MIAC: median 24.7 pg/mL, p = 0.28; with IAI: median 27.3 pg/mL vs. without IAI: median 25.1 pg/mL, p = 0.80) than women without those complications. No associations between amniotic fluid IL-6 concentrations, gestational age at sampling, and cervical fluid calreticulin and cathepsin-G concentrations were found. CONCLUSIONS: Cervical fluid calreticulin and cathepsin-G concentrations did not reflect the presence of MIAC or IAI in women with PPROM.
Keywords: chorioamnionitida; dospělí; Fetal Membranes, Premature Rupture; Sensitivity and Specificity; Humans; Biomarkers; ženské pohlaví; prospektivní studie; Calreticulin; Gestational Age; Enzyme-Linked Immunosorbent Assay; předčasný odtok plodové vody; kathepsin G; Chorioamnionitis; biologické markery; kalretikulin; senzitivita a specificita; Adult; Amniotic Fluid; Prospective Studies; Interleukin-6; těhotenství; plodová voda; Pregnancy; Cathepsin G; mladý dospělý; lidé; Young Adult; ELISA; interleukin-6; gestační stáří; Female